The Result Implementation Of Finger Hold On Laparatomy Post-Operative Patients at The HCU Cempaka Room Of Dr. Moewardi Regional General Hospital (RSUD) in Surakarta - Maiyun, Niken Palupy; Prajayanti, Eska Dwi; Wulandari, Isti (Poltekkes Kemenkes Aceh, 2024)
Background: Surgery induces changes in the body's tissue structure, triggering the body's recovery response to maintain balance (homeostasis). This process involves chemical reactions in the body that produce pain sensations in patients. Finger hold technique is a combination of deep breathing relaxation and grasping the fingers relatively quickly. The sensation experienced during the use of this technique provides a deeper sense of comfort and relaxation, as well as increasing tolerance to pain. Purpose: To determine the outcomes of applying finger hold technique on laparatomy post-operative patients at the HCU Cempaka of Dr. Moewardi Regional General Hospital (RSUD) in Surakarta. Methods: The type of research is descriptive research in the form of a case study involving 2 postoperative patients. The research instrument uses the Numeric Rating Scale (NRS) to measure the pain scale. Results: The results of the study showed that before the application of finger grip therapy, Mrs. S obtained an NRS score of 8 (severe pain), while Mrs. N obtained an NRS score of 9 (severe pain). After the application of finger grip therapy for 3 consecutive days, Mrs. S obtained an NRS score of 3, likewise for Mrs. N after the application, an NRS score of 3 was obtained. Conclusion: After applying finger grip for 3 consecutive days on Mrs. S and Mrs. N, it can be concluded that there was a decrease in the level of pain in both patients from severe pain to mild pain.